Exoskeletons for Elderly Activity of Daily Living Assistance: A Review of Upper Limb Exoskeletons and Assessments - Jalal M.F.A.; Harith H.H.; Hasan W.Z.W.; Salim M.S.F.; Lin T.-T. (Penerbit UTHM, 2025)
Population ageing is a major global issue. The elderly population aged 65 and above made up approximately 9% of the world's population in 2019, with projections indicating this will rise to 16%, or 1.5 billion individuals, by 2050. The elderly experience a natural decline in strength, endurance, agility, and flexibility. Exoskeletons have the potential to assist the elderly in daily tasks, improve mobility and balance, and provide additional strength, endurance, and capability to maintain accurate limb movement. Their application leads to a more independent and autonomous life, fostering healthy ageing and ageing in place. However, their development requires thorough considerations of functionality and user experience criteria, such as addressing the alignment with human joints, social acceptance, and motivation for exoskeleton usage. This review presents an overview of upper-limb exoskeletons designed to assist the elderly in activities of daily living, focusing on exoskeleton types and assessments. Eighteen upper limb exoskeletons were identified from the literature and categorised based on supported body segment and structure. Most of the exoskeletons are either in the embodiment design or prototyping stages and their evaluations were predominantly performed in the laboratory or simulated environment. Elderly participation in exoskeleton assessment is currently limited. There is a lack of standardized exoskeleton assessments essential for certifications, commercialization, and universal benchmarks in diverse studies. These standards would ensure consistent, repeatable, reliable, validated, and comparable findings. ? This is an open access article under the CC BY-NC-SA 4.0 license.